Baicalin and its metabolites suppresses gluconeogenesis through activation of AMPK or AKT in insulin resistant HepG-2 cells - Wang, Tao; Jiang, Hongmei; Cao, Shijie; Chen, Qian; Cui, Mingyuan; Wang, Zhijie; Li, Dandan; Zhou, Jing; Wang, Tao; Qiu, Feng; Kang, Ning (European journal of medicinal chemistry, 2017)
Scutellaria baicalensis Georgi (S. baicalensis), as a traditional Chinese herbal medicine, is an important component of several famous Chinese medicinal formulas for treating patients with diabetes mellitus. Baicalin (BG), a main bioactive component of S. baicalensis, has been reported to have antidiabetic effects. However, pharmacokinetic studies have indicated that BG has poor oral bioavailability. Therefore, it is hard to explain the pharmacological effects of BG in vivo. Interestingly, several reports show that BG is extensively metabolized in rats and humans. Therefore, we speculate that the BG metabolites might be responsible for the pharmacological effects. In this study, BG and its three metabolites (M1-M3) were examined their effects on glucose consumption in insulin resistant HepG-2 cells with a commercial glucose assay kit. Real-time PCR and western blot assay were used to confirm genes and proteins of interest, respectively. The results demonstrate that BG and its metabolites (except for M3) enhanced the glucose consumption which might be associated with inhibiting the expression of the key gluconeogenic genes, including glucose-6-phosphatase (G6Pase), phosphoenolypyruvate carboxykinase (PEPCK) and glucose transporter 2 (GLUT2). Further study found that BG and M1 could suppress hepatic gluconeogenesis via activation of the AMPK pathway, while M2 could suppress hepatic gluconeogenesis via activation of the PI3K/AKT signaling pathway. Taken together, our findings suggest that both BG and its metabolites have antihyperglycemic activities, and might be the active forms of oral doses of BG in vivo. [Display omitted] •Three metabolites of baicalin (BG) have been isolated from the urine samples of rats after oral administration of S. baicalensis.•BG, M1 and M2 enhanced the glucose consumption in insulin resistant HepG-2 cells.•BG, M1 and M2 inhibited the mRNA expression of G6Pase, PEPCK and GLUT2.•BG, M1 and M2 suppressed hepatic gluconeogenesis via AMPK or PI3K/AKT pathway.